Neurotoxicity of Titanium Dioxide Nanoparticles: A Comprehensive Review - Zhang X; Song Y; Gong H; Wu C; Wang B; Chen W; Hu J; Xiang H; Zhang K; Sun M (International Journal of Nanomedicine, 2023)
Xing Zhang,1,* Yuanyuan Song,1,* Hongyang Gong,1,* Chunyan Wu,1 Binquan Wang,1 Wenxuan Chen,2 Jiawei Hu,2 Hanhui Xiang,2 Ke Zhang,1 Mingkuan Sun1 1Department of Toxicology, School of Public Health, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 2The Second Clinical Medical School, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingkuan Sun, Department of Toxicology, School of Public Health, Nanjing Medical University, No. 101 Longmian Avenue, Jiangning District, Nanjing, 211166, People’s Republic of China, Email sunmk@njmu.edu.cnAbstract: The increasing use of titanium dioxide nanoparticles (TiO2 NPs) across various fields has led to a growing concern regarding their environmental contamination and inevitable human exposure. Consequently, significant research efforts have been directed toward understanding the effects of TiO2 NPs on both humans and the environment. Notably, TiO2 NPs exposure has been associated with multiple impairments of the nervous system. This review aims to provide an overview of the documented neurotoxic effects of TiO2 NPs in different species and in vitro models. Following exposure, TiO2 NPs can reach the brain, although the specific mechanism and quantity of particles that cross the blood-brain barrier (BBB) remain unclear. Exposure to TiO2 NPs has been shown to induce oxidative stress, promote neuroinflammation, disrupt brain biochemistry, and ultimately impair neuronal function and structure. Subsequent neuronal damage may contribute to various behavioral disorders and play a significant role in the onset and progression of neurodevelopmental or neurodegenerative diseases. Moreover, the neurotoxic potential of TiO2 NPs can be influenced by various factors, including exposure characteristics and the physicochemical properties of the TiO2 NPs. However, a systematic comparison of the neurotoxic effects of TiO2 NPs with different characteristics under various exposure conditions is still lacking. Additionally, our understanding of the underlying neurotoxic mechanisms exerted by TiO2 NPs remains incomplete and fragmented. Given these knowledge gaps, it is imperative to further investigate the neurotoxic hazards and risks associated with exposure to TiO2 NPs. Keywords: TiO2 NPs, neurotoxic effects, oxidative stress, neuronal damage, neurotoxic mechanisms